EFEKTIVITAS PENYEMBUHAN LUKA TERBUKA PADA KELINCI DARI FORMULASI SALEP EKSTRAK ETANOL DAUN BABADOTAN (Ageratum conyzoides L.) - Ferry Effendi; Halimatussa’diyah; Sri Helmina (Jurnal Farmamedika (Pharmamedika Journal), 2017)
Conyzoides ageratum L. known as babadotan leaves is herbal medicine which been used to threat a variety of diseases, including drugs open wounds. Previous research states that the ethyl acetate extract of babadotan leaves real healing effect (significant) on an open wound that is at a concentration of 40% and 80%. Based on that, do preliminary research aims to determine the effectiveness of the ointment preparations ethanolic extract of babadotan leaves (Ageratum conyzoides L.) against the open wound healing in rabbits. This type of research is a laboratory experiment. Simplicia babadotan leaf powder extracted using maceration methods. Babadotan leaf ethanolic extract ointment made within 5 concentration that is 30%, 35%, 40%, 45% and 50%. On testing ointment organoleptic test, homogeneity test, dispersive power test and pH test. Test the effectiveness of healing of open wounds using seven groups: negative control (without treatment), positive control (povidone iodine), ointments ethanol extract of babadotan leaves (SEDB) 30%, 35% SEDB, SEDB 40%, SEDB 45%, 50% SEDB against 3 white rabbits weighing 3-3.5 kg and a length of 1.5 cm open wound, was done and observed until 8 days. The data were processed statistically using One Way ANOVA (Analysis Of Variant). These results indicate that leaf ethanolic extract ointment babadotan 40%, 45% and 50% has a healing effect on open wounds in rabbits, the effect is almost similar to the positive control which leaves extract ointment babadotan with a concentration of 45%, while the ointment babadotan leaf extracts that provide the most excellent effect that an ointment at a concentration of 50%.